New insights in equine steroidogenesis: an in-depth look at steroid signaling in the placenta. Issue 1 (July 2020) - Loux, S C; Conley, A J; Scoggin, K E; El-Sheikh Ali, H; Dini, P; Ball, B A
Abstract : Steroid production varies widely among species, with these differences becoming more pronounced during pregnancy. As a result, each species has its own distinct pattern of steroids, steroidogenic enzymes, receptors, and transporters to support its individual physiological requirements. Although the circulating steroid profile is well characterized during equine pregnancy, there is much yet to be explored regarding the factors that support steroidogenesis and steroid signaling. To obtain a holistic view of steroid-related transcripts, we sequenced chorioallantois (45 days, 4 months, 6 months, 10 months, 11 months, and post-partum) and endometrium (4 months, 6 months, 10 months, 11 months, and diestrus) throughout gestation, then looked in-depth at transcripts related to steroid synthesis, conjugation, transportation, and signaling. Key findings include: 1) differential expression of HSD17B isoforms among tissues ( HSD17B1 high in the chorioallantois, while HSD17B2 is the dominant form in the endometrium) 2) a novel isoform with homology to SULT1A1 is the predominant sulfotransferase transcript in the chorioallantois; and 3) nuclear estrogen ( ESR1, ESR2 ) and progesterone ( PGR ) expression is minimal to nonexistant in the chorioallantois and pregnant endometrium. Additionally, several hypotheses have been formed, including the possibility that the 45-day chorioallantois is able to synthesize steroids de novo from acetate and that horses utilize glucuronidation to clear estrogens from the endometrium during estrous, but not during pregnancy. In summary, these findings represent an in-depth look at equine steroid-related transcripts through gestation, providing novel hypotheses and future directions for equine endocrine research.